Pengaruh Hubungan Interpersonal Terhadap Kinerja Pegawai Pada Badan Pendapatan Daerah Provinsi Maluku - Dahlan; Olivia Laura Sahertian sahertian; Maria Marlyn Tetelepta (P3M Politeknik Negeri Ambon, 2026)
This study aims to determine the influence of interpersonal relationships on employee performance at the Regional Revenue Agency of Maluku Province. This research is motivated by initial findings indicating obstacles in achieving work targets and the quality of employee output, as well as a lack of healthy social interaction in the work environment. Some employees exhibited closed attitudes, minimal cooperation, and less cordial communication, which impacted overall work effectiveness and efficiency.This research is a quantitative study with an empirical approach. The population in this study consisted of all 77 employees of the Regional Revenue Agency of Maluku Province, who were included as a sample using a saturated sampling technique. The data analysis technique used was simple linear regression.The results of the study show that interpersonal relationships have a positive and significant influence on employee performance. This means that the better the interpersonal relationships among employees, the higher the resulting performance. Conversely, poor interpersonal relationships tend to decrease employee performance. Keywords: Interpersonal Relationships; Employee Performance